An analytical study of patterns of managing organizational conflicts of some popular Sports Club Presidents in Baghdad from the perspective of their employees - Jasim Ali Mohammed; Mustafa Ismail Yasin (Journal of Applied Movement and Sport Science, 2026)
Background Sports clubs are among the most important examples of sports institutions where these organizational conflicts arise; due to the magnitude of the administrative, financial, and organizational challenges and difficulties they face, decision-makers in them must address these organizational conflicts in the best way possible if they want to be described as a successful president of the sports club. Objectives This study aimed to develop a scale for organizational conflict management styles for the presidents of popular sports clubs in Baghdad from the perspective of their employees, in order to assess the level of each of the five styles, which the researchers based on the Thomas-Kilmann (TKI) model of organizational conflict management styles. Methods The research scale was developed and applied to a sample of employees in popular sports clubs in Baghdad (administrative staff, technical staff, coaches) across (10) clubs, from which the researchers selected (200) employees as their study sample. The study sample was divided into (100) employees as a construction sample, (80) employees as a scale application sample, and (20) employees from sports clubs as an exploratory sample, representing (19.3%) of (1036) employees who make up the original population of the study of employees in sports clubs in Baghdad officially registered with the Ministry of Youth and Sports. The researchers used the descriptive method with an analytical approach due to its suitability to the nature of the study's problem, which was summarized in the variation and diversity in choosing the method and style of managing organizational conflicts by employees in sports clubs, and the absence of a prevailing pattern among them. Results After constructing the scale and applying it to the study sample, and based on what the research results revealed following statistical treatments, analysis, and discussion, the researchers concluded that there is a disparity in the levels of organizational conflict management styles in sports clubs. The style chosen by the heads of sports clubs is determined according to differences in organizational cultures and the type of conflict the clubs face, where the levels of each style (competitive, collaborative, and negotiation) appeared high, while the avoidance style was relatively low, and the adaptive style was at a moderate level. Conclusion Through the study results, the two researchers reached several recommendations, the most important of which are: the necessity of training the heads of sports clubs on various methods of managing modern organizational conflicts, and developing and enhancing the culture of dialogue and cooperation among employees within sports clubs.